Cytokine profile of oral fluid in patients with food allergy associated with atopic dermatitis and psoriasis - A. A. Barilo; S. V. Smirnova; O. V. Peretyatko (Медицинская иммунология)
The world is experiencing a rapid increase in the prevalence of allergic and autoimmune diseases. It is known that allergic inflammation is most often systemic, involving various organs and systems in the pathological process, such as the skin, respiratory and gastrointestinal tract with the development of dermatorespiratory, dermato-intestinal and other manifestations. The study of the features of the cytokine profile in oral fluid (saliva) deserves special attention, since these characteristics reflect not only local, but also systemic disorders. Of particular relevance is the study of local cytokine regulation of intercellular interactions in food allergies. Our objective was to study the concentration of IL-4, IL-10, IFNγ, secretory IgA in salivary fluid, the concentrations of total immunoglobulin E and eosinophilic cationic protein in blood serum of the patients with atopic dermatitis and psoriasis with concomitant food allergies.The study included patients with atopic dermatitis (AD, group 1, n = 20), psoriasis with concomitant food allergy (PS, group 2, n = 27), psoriasis without concomitant allergies (PS, comparison group 3, n = 23). Quantitative assessment of the cytokine concentrations (IL-4, IL-10, IFNγ, sIgA) in salivary fluid was carried out by enzyme-linked immunosorbent assay. Concentrations of total immunoglobulin E and eosinophilic cationic protein in blood serum were determined by indirect immunofluorescence. The obtained results were processed using the Statistica 8.0 applied software.In groups of patients with atopic dermatitis (Group 1) and psoriasis with concomitant food allergy (Group 2), we have noted a statistically significant increase of salivary IL-4 and IL-10, as well as of total immunoglobulin E concentrations in blood serum as compared with a group of patients with psoriasis without concomitant allergies (group 3), and with control group. When studying concentrations of IFNγ in saliva, no statistically significant intergroup differences were found. The concentration of sIgA in saliva was significantly higher in the groups of patients with atopic dermatitis and psoriasis accompanied by food allergies in comparison with control group and the group of psoriatic patients without food allergies (group 3).The cytokine profile of saliva is characterized by unidirectional changes in food allergy. Skin seems to be the shock organ in this condition, regardless of nosological form of the disease (atopic dermatitis or psoriasis). Salivary fluid is an easily accessible material when assessing the state of mucosal immunity in food allergies.